Evaluation of Customer Satisfaction Using Service Quality Demension at D'Seuhah Da Lada Restaurant - Surapranata, Hafidz; Iskandar, Budi Permadi (Journal of Business and Management, 2013)
D’Seuhah da Lada is a family restaurant that is located in Lembang, and was established to meet the needs of culinary connoisseurs of foods especially Sundanese cuisine and nuances of spicy food lovers. This restaurant has been running for about 3 years, which is necessary for a restaurant to have an evaluation and improvement in review their service quality in d’Seuhah da Lada. Previously, the study of Service Marketing in 2011, there was a final project in measuring the service quality gap of d’Seuhah da lada performance where in the result of the research, it shows that the weakness in the service quality dimension at the restaurant is the reliability, Assurance and Tangibles dimension. Based on the studies, this research focus to analyze and measure the service quality through evaluating the performance of the gap in the service quality that is crucial on the service in d’Seuhah da Lada. So for that, from the purpose of this research is to measure the influence of the service quality towards the customer satisfaction in d’Seuhah da Lada restaurant based on the dimension of Reliability, Assurance, and Tangible. The current study will be compared with the previous studies to analyze and measure the progress that has been achieved from this restaurant is anly in terms of quality service. The research method that is being used in this research is using descriptive method by distributing questionnaire with Linkert scale to customers who comes to d’Seuhah da lada then after that, this research continues the method using explorative more deeply using in depth interview towards the customer and the owner of d’Seuhah da lada in order to take the point of conclusion of this research problem. After examining the results of the process, and then it is being developed a strategy the performance evaluation in order to increase the service quality and direct the Reliability, Assurance, Tangibles dimension to improve with service recovery to be a better service, so it can be drawn into a conclusion and suggestions on the further steps ahead in a form of strategy to improve for the advancements of the service quality in d’Seuhah da Lada restaurant. Key Words: D’Seuahah da lada Restaurant, Service Quality, Service Quality Dimension, Customer Satisfaction, Service Recovery